1995
DOI: 10.1029/95jc02125
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of TOPEX/POSEIDON to the global monitoring of climatically sensitive lakes

Abstract: Remote sensing and long‐term monitoring of closed and climatically sensitive open lakes can provide useful information for the study of climatic change. Satellite radar altimetry offers the advantages of day/night and all‐weather capability in the production of relative lake level changes on a global scale. A simple technique which derives relative lake level changes is described with specific relevance to the TOPEX/POSEIDON geophysical data record data set. An assessment of the coverage and global tracking pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
241
2
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(248 citation statements)
references
References 34 publications
2
241
2
3
Order By: Relevance
“…Jason-1 is the T/P follow-on mission and has been measuring ocean surface topography since December 2001. Both T/P and Jason-1 data have also been widely used to study inland lake level variations (Birkett, 1995). Moreover, lake levels derived from satellite altimetry data are highly reliable, with errors on the order of a few centimeters (Birkett, 1995;Alsdorf et al, 2001).…”
Section: Data Usedmentioning
confidence: 99%
“…Jason-1 is the T/P follow-on mission and has been measuring ocean surface topography since December 2001. Both T/P and Jason-1 data have also been widely used to study inland lake level variations (Birkett, 1995). Moreover, lake levels derived from satellite altimetry data are highly reliable, with errors on the order of a few centimeters (Birkett, 1995;Alsdorf et al, 2001).…”
Section: Data Usedmentioning
confidence: 99%
“…For terrestrial water studies, radar altimeter-derived water levels have been long shown to be precise enough for systematic monitoring of large rivers, lakes, wetlands and floodplains (e.g., [19,[43][44][45][46]). The principle of radar altimetry is that the altimeter emits a radar pulse and measures the two-way travel time from the satellite to the surface.…”
Section: Envisat Ra-2 Radar Altimeter-derived Water Levelsmentioning
confidence: 99%
“…In this context, although not specifically dedicated for inland waters, radar altimetry represents an interesting alternative to record the in situ water level measurements in the continental environment. Indeed, satellite altimetry has been developed and optimized for open ocean and, only later, the capability of measuring water level change of continental surface reservoirs, such as inland seas and lakes, has been demonstrated [8][9][10].…”
Section: Introductionmentioning
confidence: 99%